Displaced Tibial Intercondylar Eminence Fractures - David Christopher Kieser; David Gwynne-Jones; Stephan Dreyer (Journal of Orthopaedic Surgery, 2011)
Purpose. To review outcomes of 19 patients with tibial eminence fractures. Methods. Records of 10 female and 9 male patients with type II (n=3) and type III (n=16) displaced tibial intercondylar eminence fractures were reviewed. Nine of whom were skeletally immature aged 6 to 15 (mean, 12) years; the remaining 10 patients were aged 19 to 55 (mean, 32) years. 14 involved the left knee. All patients presented with a painful haemarthrosis and reduced range of movement. Results. The most common activity causing this injury was skiing (n=7, primarily in adult females [n=5]), followed by cycling or motocrossing (n=6) and falling or other sporting activities (n=6). The injury mechanisms entailed forced flexion with rotation (n=7), hyperextension with rotation (n=7, primarily in skeletally immature males [n=4]), and direct trauma (n=5, primarily in adult males [n=4]). Eight patients (60% of adults and 22% of children) had associated injuries of the knee, which commonly occurred after direct trauma. Two patients were treated in a cast or brace after closed or open reduction without fixation. Two patients underwent arthroscopic reduction and internal fixation, and 15 underwent open reduction and internal fixation (2 after failed arthroscopic reduction and 11 proceeded directly). Postoperatively, 7 patients had a positive Lachman test, but none complained of subjective instability. Ten patients had knee stiffness; all except one had been immobilised for 4 to 6 weeks. Seven patients had extension impingement; 6 of them had been treated with open reduction and internal fixation. Two patients underwent further surgery for debridement and screw removal at years 1 and 3. One patient developed arthrofibrosis and underwent arthrolysis at month 6, but knee stiffness remained. No patient underwent subsequent anterior cruciate ligament reconstruction. Conclusion. Tibial eminence fractures are as common in adults as in children. Female skiers are at higher risk. Stiffness is a more common complication than laxity. Early range-of-motion exercise may reduce stiffness and extension impingement.